Cutaneous complications of molecular targeted therapy used in oncology - Lupu, I (J Med Life, 2016)
The new molecular targeted therapy has been developed over the past decades by using the molecular targeted molecular changes discovered in specific types of cancer. Unfortunately, most of these agents (epidermal growth factor receptors, multi-targeted small molecule tyrosine kinase inhibitors, monoclonal antibodies) have severe cutaneous adverse reactions, that not only interfere with the patient’s quality of life, but also are dose–limiting and may require treatment interruptions. These cutaneous complications and their management must be very well known by any oncologist and dermatologist who treat oncologic patients. Abbreviations: EGFR = epidermal growth factor receptors, EGFRI = epidermal growth factor receptors inhibitors